Chemical Constituents of Alpinia purpurata - Mohd Sirat, Hasnah; Liamen, Md. Rizal (Universiti Putra Malaysia Press, 1995)
The rhizomes of Alpinia purpurata collected in Universiti Teknologi Malaysia, Skudai contained an unstable labdane diterpene, labda-8 (17), 12-diene-15, 16dial and an alkaloid piperine. Their structures were established by spectroscopic methods. This is the first report on the isolation of a piperine alkaloid from an Alpinia species.